Hepatopulmonary Syndrome, A Study of Six Patients in Iraq with Literature Review - Abdullah, Aras A.; Al-Hadithi, Makki (Sulaimani Journal for Pure and Applied Sciences, 2001)
Among the pulmonary syndromes associated with liver disease is the hepatopulmonary syndrome (HPS). This is characterized by the triad of liver disease, intrapulmonary vascular dilatations (IPVD), and arterial hypoxemia (1,2). We studied six patients on the bases of clinical grounds and the available investigations in our country. English-language on case studies and series reporting results from patients with the HPS were reviewed.
Keywords: hepatopulmonary syndrome